Membangun Keterampilan Siswa dengan Memperkenalkan Teknologi dan Desain Grafis Menggunakan Photoshop - Fitria Fitria; Anhar Khalid (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
MA Nurul Islam is a private school located in Barito Kuala Regency, South Kalimantan Province. The ability of most high school students to use computer technology is still below minimum standards, especially in the field of graphic design. This can be seen in some students who take computer subjects with limited materials and facilities at the school. The aim of this service is to create MA Nurul Islam students who have knowledge and creativity in the computer field, especially for graphic design applications, as well as educate students in using graphic design applications, one of which is Photoshop. It is hoped that students can design and develop their creative talents in the field of design. This activity is carried out using a comprehensive mentoring method for MA Nurul Islam students through socializing graphic design applications using Photoshop by practicing making poster designs as objects that will be produced in this service activity. The final outcome achieved from this activity is increasing students' abilities to use computers, especially in the field of graphic design using Photoshop